2019
DOI: 10.1186/s40360-019-0356-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous exposure to vinylcyclohexene and methylmercury in Drosophila melanogaster: biochemical and molecular analyses

Abstract: BackgroundExposure to vinylcyclohexene (VCH) and methylmercury (MeHg+) can induce oxidative stress and gene modulation. Several studies have been evaluating the effects of VCH and MeHg+, but little is known about interactive effects between them. This work aimed to assess the exposure and co-exposure effects of MeHg+ and VCH on oxidative stress and gene modulation in Drosophila melanogaster.MethodsReactive species production, glutathione S-transferase (GST) and acetylcholinesterase (AChE) activities were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Using 10 mg of plants such as Mangifera indica causes GST activity to decline in Drosophila(Etuh et al, 2019). It can cause an increase or decrease in GST activity depending on the experimental model and the texture analyzed(Piccoli et al, 2019). In this study was found that while resistance decreased with the use of oil and PSM in the larval stage, GST activity decreased because of nutrition with HFD + PSM despite the formation of resistant individuals at the pupal stage.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Using 10 mg of plants such as Mangifera indica causes GST activity to decline in Drosophila(Etuh et al, 2019). It can cause an increase or decrease in GST activity depending on the experimental model and the texture analyzed(Piccoli et al, 2019). In this study was found that while resistance decreased with the use of oil and PSM in the larval stage, GST activity decreased because of nutrition with HFD + PSM despite the formation of resistant individuals at the pupal stage.…”
mentioning
confidence: 62%
“…ambrosioides L. plant extracts can negatively affect Drosophila development and resistance(Wohlenberg and Lopes-da Silva, 2009). Which is more common in older and resistant individuals GST is a detoxifying enzyme and resistance enzyme(Piccoli et al, 2019). Using 10 mg of plants such as Mangifera indica causes GST activity to decline in Drosophila(Etuh et al, 2019).…”
mentioning
confidence: 99%
“…Drosophila has been used to study the toxicity of xenobiotics 18 . Daily exposure of DM to the graded concentration up to 2000% human adult dose of silymarin had no adverse effects during the treatment period (Figure 1), suggesting that silymarin has wide safety and therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was prepared as previously described. [ 17 ] After the treatment, 20 flies were cryoanesthetized, and their heads were separated from the body. Heads and body were homogenized with 200 µL of 100 mM potassium phosphate buffer (TFK) pH 7.5 and centrifuged at 13.000 rpm for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%